PENGARUH 1,4-BUTANDIOL SEBAGAI POLIOL PADA MODIFIKASI EPOKSI MENGGUNAKAN POLIURETAN - Muhammad Ghozali; Agus Haryono; Asep Handaya Saputra; Evi Triwulandari (Research Center for Chemistry - LIPI, 2015)
Corrosion is a natural phenomenon causing degradation value and function of material. The use of paints and polymer coatings is the most popular method to protect material against corrosion. Polymer coatings used was an epoxy-based organic resin and polyurethane. Generally, those coating materials were used separately. This study carried out the modification of epoxy with polyurethane in order to obtain coating materials as a combination of epoxy and polyurethane. Expectedly, the chemical reaction between epoxy coating-material and polyurethane could improve the characteristics of the obtained coating materials. Synthesis of polyurethane-modified epoxy with 1,4-butanediol as the polyol (ETP-BTD) was conducted by reacting epoxy resin, tolonate and 1,4-butanediol simultaneously at 50 oC for 30 min with dibutyltindilaurate as catalyst. Functional group analysis of ETP-BTD was performed by Fourier Transform Infra Red (FTIR), tensile strength by Ultimate Testing Machine (UTM), adhesion by ASTM D4541 Portable Pull-off Adhesion Testers, water vapor transmission rate by ASTM E96 Desiccant Method and thermal stability was studied using Thermogravimetric Analysis (TGA). The FTIR analysis results showed that there are urethane bonds at 1716-1690 cm-1. These results showed that modification of epoxy using polyurethane increased the tensile strength and adhesion, and also decreased the water vapor transmission rate of epoxy.Â Keywords: epoxy, modification, polyol, polyurethane, 1.4-butanediol